Ansiedad y su influencia en una persona amputada del miembro inferior derecho por un accidente automovilístico en el Hospital Dr. Abel Gilber Pontón - Guachichulca Espinoza, Kelly del Rocío (2021)
Going through an experience of amputation of a part of the body produces important changes both physically and psychologically in the affected individual. In this case study, an exhaustive bibliographic review was carried out in a detailed way with the aim of fully describing the different psychosocial aspects that are part of said experience and, in the same way, suggesting the different techniques that will be applied to the patient in the process. psychotherapeutic. Among the different variables that were affected we can find; the adaptation of the patient to her environment, the management of the sensation of pain, the presence of phantom limb syndrome, alterations in self-image, expression of emotions and self-concept, and similarly the presence of depressive and anxious symptoms. To carry out the research, techniques were used to collect information, such as interviews, observation, psychometric batteries and later a psychotherapeutic scheme was designed, which is the plan that is followed to work with the patient, where techniques are used. cognitive behavioral that allows us to recognize the thoughts that disturb the patient and treat anxiety.